The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5sc00753d
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of bicyclo[3.n.1]alkanes by chiral phosphoric acid-catalyzed desymmetrizing Michael cyclizations

Abstract: 2,2-Disubstituted cyclic 1,3-diketones containing a tethered electron-deficient alkene undergo chiral phosphoric acid-catalyzed desymmetrizing Michael cyclizations to give bridged bicyclic products in high enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…We then tested dehydrating agents as additives, in order to increaset he catalyst activity.A ctivated molecular sieves (3, 4, or 5)g ave scarcely reproducible results, and surprisingly shifted occasionally the reaction pathway towards the open-chain adduct 3'a. [21] The obtainment of 3'a allowed us to perform ac ontrol experiment (see the Supporting Information) confirming the expected [12] and computed (Figure 2) incapability of the catalyst to resume 3'a to 3a.I nstead, we found that MgSO 4 as drying agent had ab eneficial effect, allowing ar educed cata-lyst loading and al ower reaction temperature,l eading to increasede nantioselectivity.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…We then tested dehydrating agents as additives, in order to increaset he catalyst activity.A ctivated molecular sieves (3, 4, or 5)g ave scarcely reproducible results, and surprisingly shifted occasionally the reaction pathway towards the open-chain adduct 3'a. [21] The obtainment of 3'a allowed us to perform ac ontrol experiment (see the Supporting Information) confirming the expected [12] and computed (Figure 2) incapability of the catalyst to resume 3'a to 3a.I nstead, we found that MgSO 4 as drying agent had ab eneficial effect, allowing ar educed cata-lyst loading and al ower reaction temperature,l eading to increasede nantioselectivity.…”
supporting
confidence: 68%
“…In principle, the PA catalyst should be able to easily "quench" this speciest hroughp rotonation,d ue to its acidity. [12] Indeed, the presence of ac ompetition between nitro-Michael and "quenching" pathways was revealed by the exclusive formationo ft he side product 3' not only in the reaction with indole 1b featuring aw eak ester Michael acceptor, but also with 1c bearing an N-acyl pyrrole, an efficientm oiety for nitro-Michael reactions (Figure 1c). [13] It is worth stressing that only few exampleso fo rganocatalytic domino reactions [14] have dealt with this type of sequential process (H-bond-promoted addition of an eutraln ucleophile triggeringasubsequent transformation), [15] none of whichh as involved ap hosphoric acid as catalyst.Prior to embarking on the study ando ptimization of the reaction, we decidedt or esortt oacomputational approacht o shed some light on the reactionp athway of this unusual phos- [a] S.…”
mentioning
confidence: 99%
“…[13] In 2015, the Lam research group reported the enantioselective desymmetrization of α,β-unsaturated enone tethered 2,2-disubstituted cyclic 1,3-diones 28 or 29 by chiral phosphoric acid-catalyst C11 mediated Michael addition (Scheme 17). [27] This method provides access to bicyclo[3.2.1]octanes 30 and bicyclo[3.3.1]nonanes 31 containing three stereocentres including one all-carbon quaternary stereocentre with good to excellent enantioselectivity, diastereoselectivity, and yields.…”
Section: P-chiral Organocatalysismentioning
confidence: 99%
“…Simultaneously, the group of Lam described the last example of desymmetrization by IMMR that did not use cyclohexadienones as starting materials [16] . In this case, they catalyzed the desymmetrization of 2,2‐disubstituted cyclic 1,3‐diketones 19 bearing α,β‐unsaturated ketones with chiral BINOL phosphoric acid VI , in cyclohexane at 50 °C, to afford bicyclo[3.2.1]‐octanes and bicyclo[3.3.1]nonanes 20 in generally high yields (especially with ketones without enolizable protons as Michael acceptors), and with good to excellent enantioselectivities, but with variable levels of diastereocontrol.…”
Section: Desymmetrization Via Organocatalytic Enantioselective Intramolecular Michael Reaction (Immr)mentioning
confidence: 99%